On the origin of mosaicity in directionally solidified Ni-base superalloys. (15th September 2021) - Strickland, Joel; Nenchev, Bogdan; Tassenberg, Karl; Perry, Samuel; Sheppard, Gareth; Dong, Hongbiao; Zhang, Ruiyao; Burca, Genoveva; D'Souza, Neil
Abstract: This article addresses the formation of low angle grain boundaries which give rise to mosaicity, a phenomenon that has only recently received attention in the single crystal Ni-base superalloy field. In this work, post-mortem advanced microscopy characterisation techniques are employed to deduce the dendrite tip growth kinetics from transverse sections of a single crystal turbine blade. As a result, it has been possible to highlight the role of isotherm curvature in inducing lateral macro-segregation parallel to a growing solidification front. Using crystallographic data from time-of-flight energy-resolved neutron imaging and novel Bragg-dip post processing, it is established that lateral macro-segregation induces small angle grain boundaries which gives rise to mosaicity within single crystal Ni-base superalloys. Mosaicity demonstrates good correlation with the local primary spacing, where faster growing dendrites demonstrate greater deviation of 〈001〉 from the casting direction, as compared with those growing at a slower rate. In light of these findings, the origin of mosaicity and its implication to secondary grain formation is discussed. Graphical abstract: Image, graphical abstract